920 Complications of Facial Cosmetic Botulinum Toxin an Injections: A Systematic Review and Meta-Analysis. (19th August 2022) - Zargaran, D; Zoller, F; Zargaran, A; Rahman, E; Woollard, A; Weyrich, T; Mosahebi, A
Abstract: Aim: Botulinum toxin A (BoNT-A) injections are a popular non-surgical procedure for facial rejuvenation with increasingly pervasive use in cosmetic clinical practice. This study analyzes the safety profile of cosmetic glabellar and forehead BoNT-A injections and assesses the influence of the practitioner factor and BoNT-A type on the complication rate. Method: A systematic search of MEDLINE and EMBASE was performed for studies reporting complications after cosmetic BoNT-A injections glabellar or in the forehead region. A random effects meta-analysis was carried out to assess complication rate. Where there were sufficient Randomized-Controlled Trials (RCTs) a network meta-analysis was performed. Results: Of 556 identified articles, 24 were included in the final quantitative analysis with 4, 268 BoNT-A injection sessions and 1, 234 placebos. Frequently observed treatment-related complications in the BoNT-A intervention group included headache, local skin reactions and facial neuromuscular symptoms. Overall BoNT-A complication rate was 16%. The odds ratio of developing complications from Abobotulinum toxin injections compared to placebo was 1.62 [1.15, 2.27; p>0.05]. The odds ratio of developing complications from Onabotulinum toxin injections compared to placebo was 1.34 [0.52, 3.48; p>0.05]. In 30% of studies the injectors were doctors, whilst in the remaining 70% the training status of practitioners was not reported. Conclusions: Cosmetic BoNT-A injections in the glabellar and forehead region appear to be safe and the majority of complications are mild and transient. Nevertheless, the literature demonstrates heterogeneous reporting of complications and a lack of consistency of the definition of treatment-related complications.